Analysis of Occupational Health and Safety (OHS) Using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) Method at the Tunas Toyota Balaraja Workshop: - - Muklis, Nurmuklis Sugianto; Ramdani, Sulaeman Deni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Work accidents can occur in any work activity. Work accidents can be caused by worker negligence or inappropriate tools used in a procedure. The aim of this research is to identify the possibility of work accidents occurring so that they can be prevented. This research uses the HIRARC (Hazard Identification Risk Assessment and Risk Control) process to identify hazards, calculate threats, and manage impacts to prevent industrial accidents. This research was conducted at Tunas Toyota Balaraja which is located on Jl. Raya Serang No. Km 24, Balaraja, Kec. Balaraja, Tangerang Regency, a company that operates in the field of car sales and vehicle servicing. The research process took 40 working days and saw firsthand all the activities at Tunas Toyota Balaraja. Tunas Toyota Balaraja is a company that sells and repairs four-wheeled cars. Car maintenance is a task that is carried out when the car is damaged. This task is not performed every day and only incidentally if the car breaks down. Car maintenance can be divided into three categories: mechanical maintenance, interior, and repairs. The results obtained in this research indicate that Tunas Toyota Balaraja has gaps in the risk identification process due to a lack of knowledge about work safety and the results of the data obtained show that every work activity in the Tunas Toyota Balaraja workshop has a high level of work risk. Because the activities here are directly related to materials that contain chemicals such as oil, battery water, radiator water, brake fluid. direct contact with gasoline, this risk of course causes economic losses. Therefore, all mechanics strive to use complete PPE on all high-risk work. Vehicle maintenance activities are divided into two activities, namely car repairs if problems occur and periodic maintenance activities based on the distance traveled by the car. In this activity there are 9 high risks, 7 medium risks, and 1 low risk. The high risk comes from potential dangers such as slipping, head injuries, scalded hands due to direct contact with hot oil, electric shock when charging the battery. Control in the form of eliminating all forms of work hazards, technical supervision and training, administrative control in the form of providing funnels when pouring oil to avoid oil spills and PPE by wearing rubber gloves. Moderate risk is caused by eye irritation and hand injuries from sharp objects. Risk control is carried out in the form of elimination, engineering and management techniques in the form of mechanical safety guarantees and pre-work safety meetings.